Effects of apnoea training on aerobic and anaerobic performance: A systematic review and meta-analysis - de Asís-Fernández, Francisco; Sereno, Daniel; Turner, Anthony P.; González-Mohíno, Fernando; González-Ravé, José María (Frontiers in Physiology, 2022)
Background Trained breath-hold divers have shown physiological adaptations that might improve athletes’ aerobic and anaerobic performance. Objective This study aimed to systematically review the scientific literature and perform a meta-analysis to assess the effects of voluntary apnoea training on markers of anaerobic and aerobic performance, such as blood lactate and VO2max. Methods A literature search on 3 databases (Web of Science, PubMed and SCOPUS) was conducted in March 2022. The inclusion criteria were (1) peer-reviewed journal publication; (2) clinical trials; (3) healthy humans; (4) effects of apnoea training; (5) variables included markers of aerobic or anaerobic performance, such as lactate and VO2max. Results 545 manuscripts were identified following database examination. Only 7 studies met the inclusion criteria and were, therefore, included in the meta-analysis. 126 participants were allocated to either voluntary apnoea training (AT; n = 64) or normal breathing (NB; n = 63). Meta-analysis on the included studies demonstrated that AT increased the peak blood lactate concentration more than NB (MD = 1.89 mmol*L-1 [95% CI 1.05, 2.73], z = 4.40, p < 0.0001). In contrast, there were no statistically significant effects of AT on VO2max (MD = 0.89 ml*kg-1*min-1 [95% CI -1.23, 3.01], z = 0.82, p = 0.41). Conclusions AT might be an alternative strategy to enhace anaerobic performance associated with increased maximum blood lactate; however, we did not find evidence of AT effects on physiological aerobic markers, such as VO2max.